PERANCANGAN BOOKLET PROMOSI PONDOK PESANTREN BUYA HAMKA MANINJAU SUMATRA BARAT - ADDINUR RAHMAH, Ir. Drs. Heldi, M.Si, Drs. Syafwan, M.Si (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Number santriwan and satriwati applying to Islamic Boarding Buya Hamka is not optimal. One of the suspected causes for lack of knowing where Buya Hamka Boarding Schools. Previous boarding school has never pass up promotions. Boarding School Buya Hamka Maninjau West Sumatra need a media campaign as an increase to be more known by people outside of West Sumatra with the hope of increasing the number of students enrolling at boarding school Buya Hamka Maninjau West Sumatra.Data analysis method used is the method of analysis 5W +1 H The purpose of this final report, is to provide information about boarding Buya Hamka Maninjau West Sumatra. Booklet is selected as the primary because more communicative and representative as a promotional media. This promotion is also added to some media support.Keywords: Design, booklets, promotional, Buya HAMKA Boarding Schools